Epigenetic mutations in 11p15 in Silver-Russell syndrome are restricted to the telomeric imprinting domain. Issue 7 (19th October 2005) - Eggermann, T; Schönherr, N; Meyer, E; Obermann, C; Mavany, M; Eggermann, K; Ranke, M B; Wollmann, H A
Abstract : Introduction: Silver-Russell syndrome (SRS; also know as Russell-Silver syndrome) is a heterogeneous syndrome which is characterised by severe intrauterine and postnatal growth retardation and typical dysmorphic features. Recently, the first SRS patients with (epi)genetic mutations in 11p15 affecting the telomeric imprinting domain have been identified. Interestingly, opposite mutations are associated with Beckwith-Wiedemann syndrome (BWS). However, the general significance of epigenetic mutations in 11p15 for the aetiology of SRS remained unclear. Methods: We screened a cohort of 51 SRS patients for epimutations in ICR1 and KCNQ1OT1 by methylation sensitive Southern blot analyses. Results: ICR1 demethylation could be observed in 16 of the 51 SRS patients, corresponding to a frequency of approximately 31%. Changes in methylation at the KCNQ1OT1 locus were not detected. Discussion: Combining these data with those on maternal duplications in 11p15, nearly 35% of SRS cases are associated with detectable (epi)genetic disturbances in 11p15. We now have to also consider a general involvement of 11p15 alterations in growth retarded patients with only minor or without further dysmorphic features. SRS and BWS may now be regarded as two diseases caused by opposite (epi)genetic disturbances of the same chromosomal region displaying opposite clinical pictures.